Clinical cases for surgery exams - Tan, Charles T.K; Lim, Thiam-Chye; Robless, Peter A. (World Scientific, 2009)
With the objective structured clinical examination (OSCE) format, undergraduate and postgraduate teaching and examination have become efficient. Suitable for students preparing for surgical OSCEs, this title covers the different clinical scenarios that a certain condition might present.